Effect of Nb on long-term creep life of JIS SUS304HTB and JIS SUS347HTB steels – heat-to-heat variation and life assessment of stainless steels. (1st November 2016) - Abe, Fujio; Tanaka, Hideo; Murata, Masaharu
Abstract : Heat-to-heat variation in creep life has been investigated for the 9 heats of JIS SUS 304HTB (18Cr–8Ni steel) and also for the 9 heats of JIS SUS 347HTB (18Cr–12Ni–Nb steel) in the NIMS Creep Data Sheets, mainly taking the effect of Nb into account. The heat-to-heat variation in creep life of 304HTB is mainly caused by the variation in precipitation hardening due to fine NbC carbides at short times, while it is mainly caused by the variation in available nitrogen concentration, defined as the concentration of nitrogen free from AlN and TiN, at long times. The heat-to-heat variation in creep life of 347HTB is mainly explained by the variation of boron concentration, 3–27 ppm, but not by the variation of solution temperature, Nb/C atomic ratio and phosphorus concentration. Boron reduces the coarsening rate of fine M23 C6 carbides along grain boundaries, which enhances the grain boundary precipitation hardening.